PERSEPSI ORANG TUA PESERTA DIDIK TERHADAP MATA PELAJARAN PENJASORKES DI SDN 9 DESA SEI KELAMBU KECAMATAN TEBAS KABUPATEN SAMBAS - Lesi, Herlin Tia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe formulation of the problem in this study is How Parents Perceptions Learners to Learning penjasorkes in SDN 9 Village Sei Kelambu Tebas District Sambas ?. The purpose of this research is to know the perceptions of parents of learners on learning physical education of sports and health (Penjasorkes) at SDN 9 Sei Kelambu Village Tebas Subdistrict Sambas District. The method used is quantitative descriptive method. Sample amounted to 27 parents of learners while the population was as many as 108 people. Using indirect communication techniques and documentary study techniques. Data analysis is done by descriptive percentage. The results of data analysis are: 1) Parents' perceptions of the benefits of penjasorkes amounting to 76.26%, this result shows that when following the learning penjasorkes learners have shown good benefits, especially in SDN 9 Village Sei Kelambu District Tebas District Sambas, the children look very enthusiastic about learning pemas. 2) Perceptions of parents of learners on penjasorkes assessment amounted to 80.55%. This means that parents' assessment of the subject of physical and health education (penjasorkesS) is very good for their children for example can teach children respect each other, bear the risk of making mistakes in exercising, teach children to obey the rules during the game, avoid cheating in playing with his friends, practice responsible attitudes in daily life, and teaches children to accept defeat while competing.Â Keywords : Perception of Parents.